Immunoelectron microscopy of acute graft versus host disease of the skin after allogeneic bone marrow transplantation. Issue 9 (September 1993) - Takata, M; Imai, T; Hirone, T
Abstract : AIMS--To clarify the pathological mechanisms of acute cutaneous graft versus host disease (GvHD) following allogeneic bone marrow transplantation. METHODS--Skin biopsy specimens from five patients were examined by immunoelectron microscopy. A panel of monoclonal antibodies against T cell and natural killer cell subpopulations was used, including anti-CD4, -CD8, -CD16b, -CD56, -CD57, and -TCR delta 1 antibodies. RESULTS--All the specimens contained CD8+ cells, CD4+ cells, and CD56+ cells infiltrating the epidermis. Cells stained with anti-CD16b, -CD57, or -TCR delta 1 were very sparse or absent. Most of the CD8+ cells in the epidermis displayed morphological features of activated cytotoxic T lymphocytes and apposition of such cells to degenerating keratinocytes was shown. CD4+ cells outnumbered CD8+ cells in the epidermis in all five cases. Noticeable intercellular as well as intracellular oedema of keratinocytes was observed at the site of prominent CD4+ cell infiltration, suggesting that these also have a role as actual effector cells by secreting cytotoxic cytokines. CD56+ cells infiltrating the epidermis did not exhibit the characteristic ultrastructural morphology of the natural killer cells thus far examined, and their lineage remained uncertain. CONCLUSIONS--These data provide direct evidence that CD8+ cytotoxic T cells attack keratinocytes, and further suggest that CD4+ cells as well as CD56+ cells participate in the cellular pathogenesis of acute cutaneous GvHD.